The climate crisis and the global green new deal the political economy of saving the planet - Chomsky, Noam 1928-; Pollin, Robert 1950- (Verso, 2020)
"An inquiry into how to build the political force to make a global Green New Deal a reality"--
Includes bibliographical references and index
Keywords: Kapitalismus; Klimaänderung; Umweltbelastung; Green New Deal; Green movement / Political aspects; Green movement / Economic aspects; Climate change mitigation / Political aspects; Climate change mitigation / Economic aspects; Capitalism / Environmental aspects